Medicando órfãos: análise discursiva sobre as doenças raras e os pacientes a partir do laboratório farmacêutico Novartis - Holtz, Ana Catarina dos Santos (2017)
The research seeks to analyze how the pharmaceutical industry builds the discourse on rare diseases and their patients. Taking the Orphan Drug Act, which guarantees benefits for medicines for such diseases, also called orphan drugs, the first chapter seeks to understand the creation of this market and to base the concepts of power, life, speech and governmentality, based on a documental and bibliographical research. The second chapter aims to reflect on the biopolitical strategies that operate in the discursive construction of the concepts of health and patient in the contemporary neoliberal scenario, while the third analyze the discourse of pharmaceutical company Novartis, the sales leader of the orphan drug segment, to understand how the laboratory establishes its institutional and commercial communication regarding rare diseases and their patients. The laboratory discourse exposes the vulnerability of the untreated patient and seeks to create a model of behavior for their rare disease patients. The theoretical foundation is formed by: Michel Foucault; Nikolas Rose; Giorgio Agamben; Didier Fassin; Peter Miller; Carlos Novas; Adriana Petryna; Paul Rabinow; Adele Clarke; Aidar Prado; Peter Pàl Pelbart; Paulo Vaz; Kátia Lerner; Paula Sibilia and Rogério da Costa